2007
DOI: 10.5380/abpr.v36i0.9804
|View full text |Cite
|
Sign up to set email alerts
|

<htm>Estrutura populacional de <i>Mimagoniates microlepis </i>(Steindachner, 1876) (Characidae, Glandulocaudinae) em um riacho de Floresta Atlântica, Paraná (Brasil)</htm>

Abstract: Estrutura populacional de Mimagoniates microlepis (Steindachner, 1876) (Characidae, Glandulocaudinae) em um riacho de Floresta Atlântica, Paraná (Brasil)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…It was found that larger individuals were abundant in the upstream sections, and smaller juveniles were abundant in the downstream section (MAZZONI et al 2004). This same distribution pattern was reported for Mimagoniates microlepis (Steindachner, 1877) in a coastal stream in the state of Paraná, Brazil (BRAGA et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…It was found that larger individuals were abundant in the upstream sections, and smaller juveniles were abundant in the downstream section (MAZZONI et al 2004). This same distribution pattern was reported for Mimagoniates microlepis (Steindachner, 1877) in a coastal stream in the state of Paraná, Brazil (BRAGA et al 2007).…”
Section: Discussionsupporting
confidence: 57%
“…This pattern was observed for Hypostomus punctatus, Astyanax janeiroensis, Deuterodon langei, Geophagus brasiliensis, and Mimagoniates microlepis (Menezes & Caramaschi, 2000;Mazzoni & Lobón-Cerviá, 2000;Braga et al, 2007;Vitule et al, 2008a). This is probably a pattern derived mainly by ecological factors with low phylogenetic interference.…”
Section: Ontogenetic Migrationmentioning
confidence: 56%
“…A population of M . microlepis from a tributary of Rio Paranaguá, PR, Brazil, not only showed a well‐defined reproductive period from winter to spring, but also showed mature males in 7 months and mature females in 9 months (Braga et al ., , , ) indicating a long reproductive season. In both cases, the long reproductive period associated with a reproductive peak in the colder months distinguishes the reproductive strategy of this species compared with most Characiformes (Azevedo, ).…”
Section: Discussionmentioning
confidence: 99%